Neglected Australian Arboviruses Associated With Undifferentiated Febrile Illnesses - Gyawali, Narayan (Front Microbiol, 2019)
Infections with commonly occurring Australian arthropod-borne arboviruses such as Ross River virus (RRV) and Barmah Forest virus (BFV) are diagnosed routinely by pathology laboratories in Australia. Others, such as Murray Valley encephalitis (MVEV) and Kunjin (KUNV) virus infections may be diagnosed by specialist reference laboratories. Although Alfuy (ALFV), Edge Hill (EHV), Kokobera (KOKV), Sindbis (SINV), and Stratford (STRV) viruses are known to infect humans in Australia, all are considered ‘neglected.’ The aetiologies of approximately half of all cases of undifferentiated febrile illnesses (UFI) in Australia are unknown and it is possible that some of these are caused by the neglected arboviruses. The aims of this study were to determine the seroprevalence of antibodies against several neglected Australian arboviruses among residents of Queensland, north-east Australia, and to ascertain whether any are associated with UFI. One hundred age- and sex-stratified human plasma samples from blood donors in Queensland were tested to determine the prevalence of neutralising antibodies against ALFV, BFV, EHV, KOKV, KUNV, MVEV, RRV, SINV, and STRV. The seroconversion rates for RRV and BFV infections were 1.3 and 0.3% per annum, respectively. The prevalence of antibodies against ALFV was too low to enable estimates of annual infection rates to be determined, but the values obtained for other neglected viruses, EHV (0.1%), KOKV (0.05%), and STRV (0.05%), indicated that the numbers of clinical infections occurring with these agents are likely to be extremely small. This was borne out by the observation that only 5.7% of a panel of 492 acute phase sera from UFI patients contained IgM against any of these arboviruses, as detected by an indirect immunofluorescence assay. While none of these neglected arboviruses appear to be a cause of a significant number of UFIs in Australia at this time, each has the potential to emerge as a significant human pathogen if there are changes to their ecological niches.